Economic Characteristics and Subjective Well-Being - Tomáš Želinský; Tatiana Soroková; Daniela Petríková (Sociológia / Slovak Sociological Review, 2018)
The primary objective of this study is to examine the relationship between economic characteristics and well-being as one of the components of quality of life. The study is based on microdata obtained from a representative EU-SILC 2013 survey covering the Slovak population age 16 and older. Subjective wellbeing is proxied by a score reflecting the general mood or affect, including depression, anxiety, and psychologic well-being. The estimated mean value of the total subjective wellbeing score is 70 (median: 73). The results presented in this study suggest that economic factors are strongly correlated with the level of subjective well-being. The findings propose positive and diminishing returns to income; unemployed people score on average approximately 9 points lower than those who are employed; people living in indebted households have a lower level of subjective well-being than those living in households without debts; and the ability to face unexpected financial expenses increases the level of well-being.
Keywords: I31; I30; 330; Well-Being; EU-SILC; economic characteristics; Slovakia